A price worth paying? Accountability, red tape and the regulation of affordable housing. Issue 4 (December 2014) - Travers, Max
Abstract : Although it is not a pressing social problem in the same way as, for example, poverty, child abuse, or climate change, red tape causes frustrations for many working in public and private sector organisations, perhaps even more than for the ordinary citizen dealing with large government agencies. This paper will explore some dimensions of this contentious issue. It will consider the positive view of regulation advanced by regulation theorists, and some qualitative researchers associated with this tradition. Drawing on a qualitative research study concerning the regulation of affordable housing in Australia, it examines the nature of administrative burdens. It is suggested that three factors lead to the perception of red tape: whether regulation is seen as making a difference to services beyond accountability; whether the measures used are meaningful; and the resources available for compliance. Qualitative researchers can help those in government seeking to reduce administrative burdens by supplying realistic accounts that address the views and experiences of those subject to regulation.